2016
DOI: 10.1002/ange.201510866
|View full text |Cite
|
Sign up to set email alerts
|

Re‐engineering the Immune Response to Metastatic Cancer: Antibody‐Recruiting Small Molecules Targeting the Urokinase Receptor

Abstract: Developing selective strategies to treat metastatic cancers remains a significant challenge. Herein, we report the first antibody-recruiting small molecule (ARM) that is capable of recognizing the urokinase-type plasminogen activator receptor (uPAR), a uniquely overexpressed cancer cellsurface marker, and facilitating the immune-mediated destruction of cancer cells. A co-crystal Correspondence to: David A. Spiegel. Supporting information for this article is available on the WWW under http://dx.doi.org/10.1002/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…The urokinase-type plasminogen activator receptor (uPAR) expression is reported to be substantially upregulated in invasive cancer cells compared to healthy cells or benign tumors 25 . We confirmed the overexpression of uPAR in MDA-MB-231 cells, which showed almost 5.6-fold higher expression than non-carcinoma HEK-293 cells ( Figure S16 ), consistent with previous studies 37 . Inspired by the relatively high expression of uPAR in MDA-MB-231 cells, we conjugated hexynoic uPA peptide, a specific ligand to uPAR, onto N 3 -PEG 5k -pPhe(15) copolymer via click reaction for TNBC targeting.…”
Section: Resultssupporting
confidence: 92%
“…The urokinase-type plasminogen activator receptor (uPAR) expression is reported to be substantially upregulated in invasive cancer cells compared to healthy cells or benign tumors 25 . We confirmed the overexpression of uPAR in MDA-MB-231 cells, which showed almost 5.6-fold higher expression than non-carcinoma HEK-293 cells ( Figure S16 ), consistent with previous studies 37 . Inspired by the relatively high expression of uPAR in MDA-MB-231 cells, we conjugated hexynoic uPA peptide, a specific ligand to uPAR, onto N 3 -PEG 5k -pPhe(15) copolymer via click reaction for TNBC targeting.…”
Section: Resultssupporting
confidence: 92%
“…Saltbridge interactions are commonly found in small-molecule protein-protein interaction inhibitors. We have previously shown that disruption of the uPAR•uPA protein-protein interaction by IPR-803 was completely dependent on a salt bridge (46) that was later independently confirmed by crystallography (47). To confirm the importance of the salt bridge, we used the FP assay to test whether a methyl ester precursor of 6, namely 7 (BTT-269) or 2 (BTT-245), a ketone derivative of 1, binds to Ca V β 3 .…”
Section: Resultsmentioning
confidence: 79%
“…DNP is a hapten that is bound by 1% of endogenous human antibodies, 67 and has been employed in several immune-recruiting therapeutics to recruit antibodies to various pathogens 26,39,40 and cancer cells. 68,69 We hypothesized that, once the AR-PCC binds to the K. pneumoniae surface, the AR handle should recruit antibodies to the pathogen. PCCs were tagged with a DNP group via conjugation of a DNP-modied lysine residue, in which a DNP moiety is covalently attached at the terminal sidechain amine.…”
Section: Ar-pcc-driven Opsonization Of K Pneumoniaementioning
confidence: 99%